Perancangan Media Pembelajaran Berbasis Augmented Reality pada Pembelajaran Matematika untuk Kelas VIII di MTsN 2 Pasaman - Sani, Rafika; Efriyanti, Liza; Supriadi, Supriadi; Derta, Sarwo (Institut Teknologi Pendidikan Indonesia, 2022)
This research was conducted from the problems that the authors found during observations at MTsN 2 Pasaman which so far the teacher has not maximized the use of technology in learning mathematics, students only rely on learning from the teacher verbally, so students get bored quickly when learning takes place and have difficulty understanding the material taught by the teacher. Therefore, the authors design learning media based on Augmented Reality so that it can be an alternative learning media. The purpose of this research is to produce an Augmented Reality-based supporting media design for mathematics learning that is valid, practical and effective. The method used in this study is the Research andDevelopment (R&D) method using the Luther-Sutopo version of the Multimedia Development Life Cycle (MDLC), which consists of six stages, namely concept (conception), design (design), collecting material (material collection). assembly (manufacture), testing (testing), and distribution (distribution). And the product test was carried out in this study, namely the validity test given to lecturers of field experts or field experts, practicality tests carried out by mathematics subject teachers and effectiveness tests given to students at MTsN 2 Pasaman class VIII. Based on the results of product tests that have been carried out by the author of the validity test, the average value is 0.84 which is declared valid, for the practicality test, the average value is 0.88 which is declared practical and for the effectiveness test, the average value is obtained. the average is 0.87 which is declared effective.